A COMPARISON OF HYDROGEN PRODUCTION BY ELECTROLYSIS METHOD USING WATER ELECTROLYTE WITH STAINLESS STEEL AND COPPER ELECTRODES - Afisna, Lathifa Putri; Kolala, Putra Andi; Meha, Gabriel; Pasaribu, Frans Winner; Sindhu, I Gede Pande Naraya (Department of Mechanical Engineering Education, 2024)
This experiment focuses on the production of hydrogen gas (H2) using the electrolysis method. The electrolysis method converts water (H2O) into the combustible compound H2 and O2, which aids in the combustion process. Hydrogen gas (H2) is an important renewable energy source. Therefore, research is needed to explore and optimize alternative and renewable energy sources, one of which is hydrogen gas. The objective of this experiment was to find the optimal variation between stainless steel and copper in producing the highest hydrogen gas pressure. In this experiment, a power source of 12 V 20 A was used, along with a salt solution of 1500 mL with a concentration of 0.167 gr/mL. Two different types of cathodes were used, stainless steel and copper. The experiment involved variations in the number of plates, namely 3, 5, and 7, and testing durations of 5, 10, and 15 minutes. The test results indicated that the hydrogen gas pressure increased with the increasing number of plates and electrolysis time. The highest pressure was achieved using copper plates with 7 plates and an electrolysis time of 15 minutes. Under these conditions, the hydrogen gas pressure reached 439.677 Pa